1996
DOI: 10.1021/bi9622433
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Deletion Mutants of Troponins I and T:  COOH-Terminal Truncation of Troponin T Abolishes Troponin I Binding and Reduces Ca2+ Sensitivity of the Reconstituted Regulatory System

Abstract: The interaction between troponin I (TnI) and troponin T (TnT) remains the least understood binary interaction among the regulatory proteins of vertebrate striated muscle. To identify the specific binding domains of TnI and TnT and to evaluate the interactions of TnT with troponin C and tropomyosin (Tm), we generated an NH2-terminal fragment of human fast skeletal beta TnT (TnT1-201; residues 1-201) using site-directed mutagenesis. The mutant protein failed to bind to rabbit skeletal muscle TnI as judged by HPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…Recently, Jha et al (6) showed that the deletion of 57 carboxyterminal residues of TnT eliminates TnI binding. Our results showing the involvement of HR domains of TnT and TnI in binary interaction are consistent with the above-mentioned reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Jha et al (6) showed that the deletion of 57 carboxyterminal residues of TnT eliminates TnI binding. Our results showing the involvement of HR domains of TnT and TnI in binary interaction are consistent with the above-mentioned reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, the structural basis for its role in this process is not clear. Recent mutagenesis studies have identified the region of fast skeletal TnT that contributes to the Ca 2ϩ sensitivity of the thin filament-based regulatory system (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblotting, cross-linking and competitive labeling studies on the rabbit fast skeletal TNI and TNT suggest that the TNI 58-107 segment bound to TNT [22][23][24]. The atomic structure of the human cardiac troponin core complex shows that the helical part of H2 (I) interacted to H2 (T2) [4].…”
Section: 2 Molecular Interactions Between the Tni And Tnt Isoformsmentioning
confidence: 99%
“…Studies of TnT structure-function relationships have revealed that the COOH-terminal T2 fragment of TnT binds to the central region of Tm, whereas the central region of the TnT polypeptide has been shown to interact with the head-to-tail overlapping region of Tm (13)(14)(15)(16). The COOHterminal T2 region of TnT also anchors the TnI-TnC binary complex formation in a direct, Ca 2ϩ -independent manner (17,18). Resonance energy transfer experiments showed that TnT, but not TnC, caused an elongation of the TnI molecule (19).…”
Section: Troponin T (Tnt)mentioning
confidence: 99%